Phase and structural thermal evolution of Bi–Si–O catalysts obtained via laser ablation - Shabalina, Anastasiia V.; Golubovskaya, Aleksandra G.; Fakhrutdinova, Elena D.; Kulinich, Sergei A.; Vodyankina, Olga V.; Svetlichnyi, Valerii A. (Nanomaterials)
Laser methods are successfully used to prepare complex functional nanomaterials, especially for biomedicine, optoelectronics, and heterogeneous catalysis. In this paper, we present complex oxide and composite nanomaterials based on Bi and Si produced using laser ablation in liquid followed by subsequent powder annealing. Two synthesis approaches were used, with and without laser post-treatment of mixed (in an atomic ratio of 2:1) laser-generated Bi and Si colloids. A range of methods were used to characterize the samples: UV-Vis diffusion reflection, IR and Raman spectroscopy, synchronous thermal analysis, X-ray diffraction, transmission electron microscopy, as well as specific surface-area evaluation. We also followed the dynamics of phase transformations, as well as composition, structure and morphology of annealed powders up to 800 °C. When heated, the non-irradiated series of samples proceeded from metallic bismuth, through β-Bi2O3, and resulted in bismuth silicates of various stoichiometries. At the same time, in their laser-irradiated counterparts, the formation of silicates proceeded immediately from the amorphous Bi2SiO5 phase formed after laser treatment of mixed Bi and Si colloids. Finally, we show their ability to decompose persistent organic molecules of Rhodamine B and phenol under irradiation with a soft UV (375 nm) source.